Enterprise Architecture Design for Class Approval and Scheduling Governance (Permission Planning) at Universitas Terbuka - Muhammad Rif’an; Iwan Susanto; Iswaya Maalik; Zakirman Zakirman; Erika Pradana (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Large open and distance universities must plan classes under high enrolment volatility, limited teaching capacity, and strict accountability. At Universitas Terbuka (UT), class permission planning is still carried out through fragmented tools such as spreadsheets and email-based coordination. The process becomes slow during peak periods, decisions are hard to trace, and policy rules are applied inconsistently across units. Objective: This study aims to design an academic management solution that makes class permission decisions faster and more explainable while remaining scalable for a mega-university context. Methods: A design science approach was used. The TOGAF Architecture Development Method (ADM) was adapted to produce as-is and to-be business workflows, a unified information model, and modular application and technology architectures. Requirements were collected through observation, document review, and semi-structured interviews with stakeholders from academic administration, academic units, and IT services. Results: A functional prototype (SIMPATIK) was then developed and validated through usability walkthroughs with 40 participants. Mean ratings across five indicators ranged from 4.25 to 4.55 (five-point scale), indicating strong perceived clarity, ease of use, and transparency decision. The findings suggest that an enterprise-architecture-based design can reduce manual bottlenecks and strengthen accountability for class permission planning in open and distance education. The proposed design embeds policy checks at the point of request, routes only exceptional cases to administrators, and records machine-readable explanations and audit trails for every decision. A microservice-based deployment model is specified, supported by an RDBMS cluster, cache/message queue, and observability stack to handle enrolment spikes. Conclusion: These artifacts provide a reusable blueprint for institutions facing similar scale and governance constraints.